Penyuluhan Pembukuan Keuangan Sederhana Dalam Bentuk Buku Kas Di Desa Muara Tae, Kabupaten Kutai Barat, Provinsi Kalimantan Timur - Muhammad Abadan Syakura; Nina Subgaio Achmari (UNIVERSITAS CENDERAWASIH, 2023)
Entrepreneurship is a rapidly growing profession in Muara Tae Village. However, most of the entrepeneur in Muara Tae Village still have not implemented bookkeeping for their business finances. This raises various financial problems in the future. Therefore, to overcome the risk of problems that might occur, we conduct counseling on financial accounting in the form of a simple cash book. The purpose of this activity is to provide an understanding of the importance of financial bookkeeping in the form of a simple cash book so that business people in Muara Tae Village can understand the importance of simple financial bookkeeping and can apply it in running their business. The method used is observation and counseling to residents of Muara Tae Village who have businesses. The activity began with distributing questionnaires through the Muara Tae Village SME’s WhatsApp group, preparing counseling materials, and distributing outreach invitations to SME’s. The result of this activity is an increase in the understanding of SME’s in Muara Tae Village about simple bookkeeping and they can make their own simple bookkeeping according to the business they are doing. This is expected to overcome existing problems and in accordance with the expected benefits.Keywords : entrepreneur, bookeeping, cashflow